Potassium Channel Opener Pinacidil Induces Relaxation of the Isolated Human Radial Artery - Natasa Stojnic; Ljiljana Gojkovic-Bukarica; Miodrag Peric; Leposava Grbovic; Aleksandar Lesic; Marko Bumbasirevic; Helmut Heinle (Elsevier, 2007)
Taking into consideration that the search for drugs capable of modifying blood flow through human radial artery (RA) is warranted, the present study was designed to examine the vasodilatatory effects of the potassium channel opener, pinacidil on the RA and to define the contribution of different K+-channel subtypes in the endothelium-independent pinacidil action on this blood vessel. Pinacidil relaxed the RA rings with endothelium and without endothelium with comparable potency. N-nitro-L-arginine methyl ester (L-NAME) and methylene blue did not affect the pinacidil-induced vasorelaxation in rings with endothelium. In the rings without endothelium, the K+-channel blockers glibenclamide and tetraethylammonium (TEA) moderately antagonized the pinacidil-induced relaxation, while charybdotoxin and 4-aminopiridine did not. In endothelium-denuded rings, precontracted with 100 mM K+, the relaxant responses to pinacidil were highly significantly shifted to the right compared to those obtained in RA precontracted with phenylephrine, but pinacidil-induced maximal relaxation was not affected. Addition of nifedipine did not but addition of nifedipine and nickel (Na+-Ca2+ exchanger inhibitor) did cause a statistically significant rightward shift of the pinacidil concentration-relaxation curve, although the effect 0.1 mM pinacidil was preserved. Thus, pinacidil induces relaxation of the human RA in endothelium-independent manner, and glibenclamide- and TEA-sensitive vascular smooth muscle K+ channels are probably involved. Its ability to completely relax the RA precontracted with K+-rich solution suggests that pinacidil has additional K+ channel-independent mechanism(s) of action. It seems that stimulation of the forward mode of the Na+-Ca2+ exchanger plays a part in this K+ channel-independent effect of pinacidil. Keywords:: human radial artery, pinacidil, K+ channel, Na+-Ca2+ exchanger